EVALUASI HUBUNGAN KREDIT MACET, PENYALURAN KREDIT, DAN SUSTAINABILITY REPORT PADA KEMAMPULABAAN BANK UMUM MILIK NEGARA YANG TERCATAT DI BURSA EFEK INDONESIA (BEI) - Suhendri, Hendrik; Handayanto, Adrian Junaidar; Putri, Sri Andika; Hendra, Hendra (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2024)
Purpose: This research aims to evaluate the relationships of bad credit, credit distribution, and sustainability reports on the profitability of state-owned commercial banks listed on the IDX, either partially or simultaneously., Methods: This research applies quantitative methods with the sampling technique being purposive sampling, in the end four state-owned commercial banks listed on the IDX were selected as research samples. data obtained from financial reports of state-owned commercial banks for the 2015-2022 period., Analysis data: The data was analyzed using multiple linear regression methods, Result and discussions: The research results prove that bad credit has a substantial impact on the profitability of state-owned commercial banks with a calculated t value = 4.190, exceeding t table = 2.040. Credit distribution also has an important impact on profitability with a calculated t value = 4.775, as well as sustainability reports with a calculated t value = 3.884. Simultaneously, bad loans, credit distribution, and sustainability reports have a substantial impact on the profitability of state-owned commercial banks listed on the IDX, with a calculated F value = 5.993 exceeding F table = 2.947., Conclusion: Based on the results of this research, the conclusion is that low non-performing loans, high credit disbursement, and the existence of sustainability reports contribute positively to the profitability of state-owned commercial banks. Future research could consider using variables such as company size or the number of outstanding shares.